Troponin is unrelated to outcomes in heart failure patients discharged from the emergency department - Gregory J. Fermann; Jon W. Schrock; Phillip D. Levy; Peter Pang; Javed Butler; Anna Marie Chang; Douglas Char; Deborah Diercks; Jin H. Han; Brian Hiestand; Chris Hogan; Cathy A. Jenkins; et al. (Journal of the American College of Emergency Physicians Open, 2022)
Abstract Background Prior data has demonstrated increased mortality in hospitalized patients with acute heart failure (AHF) and troponin elevation. No data has specifically examined the prognostic significance of troponin elevation in patients with AHF discharged after emergency department (ED) management. Objective Evaluate the relationship between troponin elevation and outcomes in patients with AHF who are treated and released from the ED. Methods This was a secondary analysis of the Get with the Guidelines to Reduce Disparities in AHF Patients Discharged from the ED (GUIDED‐HF) trial, a randomized, controlled trial of ED patients with AHF who were discharged. Patients with elevated conventional troponin not due to acute coronary syndrome (ACS) were included. Our primary outcome was a composite endpoint: time to 30‐day cardiovascular death and/or heart failure‐related events. Results Of the 491 subjects included in the GUIDED‐HF trial, 418 had troponin measured during the ED evaluation and 66 (16%) had troponin values above the 99th percentile. Median age was 63 years (interquartile range, 54‐70), 62% (n = 261) were male, 63% (n = 265) were Black, and 16% (n = 67) experienced our primary outcome. There were no differences in our primary outcome between those with and without troponin elevation (12/66, 18.1% vs 55/352, 15.6%; P = 0.60). This effect was maintained regardless of assignment to usual care or the intervention arm. In multivariable regression analysis, there was no association between our primary outcome and elevated troponin (hazard ratio, 1.00; 95% confidence interval,  0.49–2.01, P = 0.994) Conclusion If confirmed in a larger cohort, these findings may facilitate safe ED discharge for a group of patients with AHF without ACS when an elevated troponin is the primary reason for admission.